Body composition changes, metabolic fuel use and energy expenditure during extended fasting in subantarctic fur seal (Arctocephalus tropicalis) pups at Amsterdam Island - G Beauplet; C Guinet; John Arnould (2003)
The fasting metabolism of 71- to 235-d-old subantarctic fur seal ( Arctocephalus tropicalis ) pups from Amsterdam Island, southern Indian Ocean, was investigated during the long foraging trips of their mothers. Body lipid reserves were proportionally greater in female than male pups and higher in postmoult (37%) than premoult (10%) animals. The mass-specific rate of mass loss did not differ between the sexes but was lower than observed in other species. Daily mass loss was estimated to 56% fat, 10% protein, and 34% water. The rate of protein catabolism (15 g d −1 ) was negatively related to the size of initial lipid stores and accounted for 9% (±1%) of total energy expenditure. However, body composition changes during the fast were not equal between the sexes, with females relying more on protein catabolism than males (11% and 5% of total energy expenditure, respectively). Energy expenditure (270 kJ kg −1 d −1 ) and metabolic water production (11.5 mL kg −1 d −1 ) rates are the lowest reported for an otariid species. These results suggest that subantarctic fur seal pups greatly reduce activity levels to lower energy expenditure in addition to adopting protein-sparing metabolic pathways in order to survive the extreme fasts they must endure on Amsterdam Island.